Optimized Fibril Network Morphology by Precise Side‐Chain Engineering to Achieve High‐Performance Bulk‐Heterojunction Organic Solar Cells. Issue 26 (18th May 2018) - Liu, Tao; Huo, Lijun; Chandrabose, Sreelakshmi; Chen, Kai; Han, Guangchao; Qi, Feng; Meng, Xiangyi; Xie, Dongjun; Ma, Wei; Yi, Yuanping; Hodgkiss, Justin M.; Liu, Feng; et al.
Abstract: A polymer fibril assembly can dictate the morphology framework, in forming a network structure, which is highly advantageous in bulk heterojunction (BHJ) organic solar cells (OSCs). A fundamental understanding of how to manipulate such a fibril assembly and its influence on the BHJ morphology and device performance is crucially important. Here, a series of donor–acceptor polymers, PBT1‐O, PBT1‐S, and PBT1‐C, is used to systematically investigate the relationship between molecular structure, morphology, and photovoltaic performance. The subtle atom change in side chains is found to have profound effect on regulating electronic structure and self‐assembly of conjugated polymers. Compared with PBT1‐O and PBT1‐S, PBT1‐C‐based OSCs show much higher photovoltaic performance with a record fill factor (FF) of 80.5%, due to the formation of optimal interpenetrating network morphology. Such a fibril network strategy is further extended to nonfullerene OSCs using a small‐molecular acceptor, which shows a high efficiency of 12.7% and an FF of 78.5%. The results indicate the formation of well‐defined fibrillar structure is a promising approach to achieving a favorable morphology in BHJ OSCs. Abstract : Three novel polymers are synthesized to systematically investigate the relationship between molecular structure, morphology, and photovoltaic performance. A favorable fibrillar network morphology with a narrow polymer fibril width in a PBT1‐C:PC71 BM blend leads to a record fill factor exceeding 80%, indicating that the formation of a well‐defined fibrillar structure is a promising approach to achieving a favorable morphology in organic solar cells.